Placenta percreta: a successful conservative outcome - Mishra, Nigamananda; Desai, Devika; Prabhu, Santoshi; Jadhav, Vaishali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Placental adherent syndromes have been known to us since antiquity. These are very much common in the present era due to rising incidence of surgical evacuation of pregnancy, caesarean sections and hysterotomy. Thought to be due to abnormal trophoblastic invasion at the endo-myometrial junction along with vasculature leading to varying degrees of invasion and adherence, lastly including the pelvic organs. Morbidity and mortality associated with these have been an obstetrician’s nightmare and thus a good learning curve. Hence, knowing appropriate case selection and management in terms of early diagnosis, mode of delivery, dealing with obstetric emergencies and appropriate counseling has become the need of the hour. The focus being, conservative management and best perinatal outcome with least maternal morbidity